(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2023)
Risk management is a concern that affects the entire AEC (Architecture, Engineering, andConstruction) industry. Inadequate risk management may affect how cities will develop in the future,how land will be used, and how cities will be designed, in addition to making it more challenging toaccomplish the project’s goals. Due to the BIM (Building Information Modelling) and BIM-related digitaltechnologies’ rapid expansion and adoption, It is essential to do a detailed analysis of theseinnovations’ current state of the art. This article reviews the most recent technology-based riskmanagement approaches, including BIM and automatic rule checking. Knowledge-based systems andIT-based reactive and proactive safety solutions are increasingly employed in addition to traditionalrisk management methods. The results demonstrate that BIM may function as a foundation for otherBIM-based tools to conduct additional risk analysis and as a tool to support the project developmentprocess as a methodical risk assessment tool. Currently, the administration of construction workers’safety receiving the most attention, as recent efforts have mainly been concentrated on analyzingtechnology advancements.For planning, design, construction, and operation, data may be acquired, reviewed, and monitored using3D models in a coordinated and consistent manner. The creation of an intelligent 3D model is the firststep in the construction information modelling (BIM) process, which aids in decision-making forconstruction and infrastructure projects. Using this method, data organization, analysis, and recordingmay be planned, created, and used it is a process that begins with the creation of an intelligent 3D modelthat may be used to gather, evaluate, and manage data related to planning, design, construction, andoperating issues in order to better guide decision-making for infrastructure and construction projects.The paper outlines a risk management method that makes use of routine inputs, anticipated outcomes,and project experience to its advantage. The research also includes a quick evaluation of the BIMemploying Excel information technology. The system was built and the work was finished using thistechnology.